Swedish tv supply 2001 - Asp, Kent (University of Gothenburg, 2018)
The study "Swedish TV supply" is conducted annually since 1998.

The examination of the programs offered on TV is designed to answer five questions: (1) What is the range of supply in the television channels during the program year 2001? (2) What similarities and differences are there between the television channels' program profiles? (3) What are the programs offered for specific groups: children, youth, minorities and the disabled? (4) How has variety of programmes developed over time? (5) And how is diversity manifested in Swedish television?

The study is based in principle on the information about TV programme from television channels. The programs are classified using this information and starting from a predefined classification scheme. Eight broadcast channels have been examined: SVT1, SVT2, TV4, TV3, Kanal 5, ZTV, TV6 and TV8.

In this study, as in most Swedish and international studies of television programme supply from the 1950s onwards, is information-entertainment the fundamental dimension in the classification of its contents. This means broadly that on the one hand, news and facts-oriented programs and on the other - programs focusing on recreation and entertainment are distinguished. In between, a third program genre is referred to among programs, including both factual and entertainment elements within a single program. The study also has programme supply classified by the target population the programs are primarily intended for: children, young people, ethnic minority groups as well as programs specifically tailored to people with disabilities.

Purpose:

Create repeated, systematic and long-term scientific studies of the programs offered in Swedish television.

Undersökningen "Svenskt tv-utbud" sker årligen sedan 1998.

Undersökningen av programutbudet avser att besvara fem olika frågor: (1) Hur såg utbudet ut i de enskilda tv-kanalerna under programåret 2001? (2) Vilka likheter och skillnader finns mellan tv- kanalernas programprofiler? (3) Hur såg programutbudet ut till särskilda grupper: barn, ungdomar, minoritetsgrupper och funktionshindrade? (4) Hur har programutbudet utvecklats över tid? (5) Och hur ser mångfalden ut i svensk television?

Undersökningen av programutbudet utgår i princip enbart från tv-kanalernas egna programtablåer. Programmen klassificeras med hjälp av denna information och med utgångspunkt ifrån ett i förväg bestämt klassificeringsschema. Åtta sändningskanaler har undersökts: SVT1, SVT2, TV4, TV3, Kanal 5, ZTV, TV6 och TV8. I undersökningen ingick även UR:s programutbud.

I denna undersökning, liksom i de flesta svenska och utländska studier av televisionens programutbud från 1950-talet och framåt, utgör information-underhållning den grundläggande dimensionen i klassificeringen av programutbudet. Detta innebär i stora drag att å ena sidan urskiljs nyhets- och faktainriktade program och å den andra program inriktade på förströelse och underhållning. Däremellan urskiljs en tredje programgenre som brukar kallas för blandprogram därför att de utmärks av att fakta- och underhållningsbetonade inslag varvas inom ramen för ett och samma program. I undersökningen har även programutbudet i fyra avseenden klassificerats med utgångspunkt ifrån den målgrupp programmen i första hand vänder sig till: barn, ungdomar och etniska minoritetsgrupper samt om programmen är särskilt anpassade till människor med funktionshinder.

Syfte:

Skapa återkommande, systematiska och långsiktiga vetenskapliga studier av programutbudet i svensk television.
Svenskt tv-utbud 2001
Keywords: television channels; tv-kanaler; television programmes; tv-program; MEDIA, COMMUNICATION AND LANGUAGE; MEDIA, KOMMUNIKATION OCH SPRÅK; Media; Media; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap